Dimethyl fumarate transfer into human milk. (October 2020) - Ciplea, Andrea I.; Datta, Palika; Rewers-Felkins, Kathleen; Baker, Teresa; Gold, Ralf; Hale, Thomas W.; Hellwig, Kerstin
Dimethyl fumarate (DMF) is approved for the treatment of relapsing-remitting multiple sclerosis. It is unknown whether DMF or its primary metabolite monomethyl fumarate (MMF) are excreted into human milk. We present two cases of lactating patients who donated milk samples to study the transfer of MMF into human milk following a week of 2 × 240 mg daily oral dose. Samples were analyzed using liquid chromatography mass spectrometry. The calculated relative infant dose was 0.019% and 0.007%. This is the first study to demonstrate that MMF is transferred into human milk, with only limited exposure to an infant.